Continuous-wave electron paramagnetic resonance (CW-EPR) for studying structure-function relationships in a Cu-containing nitrite reductase and a Mo-containing aldehyde oxidoreductase - González, Pablo Javier (2023)
Transition metal ion-containing oxidoreductases, which carry out long-distance electron transfer reactions, are a large family of metalloproteins that are widely distributed in nature. The metal ions are either present as mononuclear centers or are organized in clusters. One of the metal cofactors is the active site of the enzyme where the substrate is converted to a product, while the others serve as electron transfer centers. Metal cofactors are paramagnetic in certain protein redox states and may additionally exhibit different relaxation rates and weak superexchange interactions transferred via intraprotein electron transfer pathways. Cu-containing nitrite reductase and Mo-containing aldehyde oxidoreductase are two representative examples of oxidoreductases in which these phenomena occur, making them interesting systems to study using electron magnetic resonance techniques. We summarize here several X-band Continuous-Wave Electron Paramagnetic Resonance (CW-EPR) studies that have allowed insights into structural and functional aspects of these two proteins and may help characterize closely related systems.